Use of IDeS Method to Design an Innovative HYICE Sportscar - Giulio Galiè; Michele Cappelli; Pietro Maffei; Matteo Robusti; Igor Vasileski; Leonardo Frizziero (Inventions, 2023)
In the contemporary automobile scene, environmental effect abatement is being increasingly sought; this demands a full rethinking of the entire system and entails more than just the reduction in exhaust pollutant emissions. Currently, the most popular approach is the electrification of automobiles, which significantly reduces pollution in major urban areas while simultaneously posing a new set of problems. The two types of zero-emission vehicles that are now being developed the most are hydrogen fuel cells and battery electric cars, but another option is the Hydrogen Internal Combustion Engine (HYICE) engine, which is highly advantageous in terms of pollutants, aside from Nitrogen Oxides (NOx), which can be considerably decreased. The purpose of this study is to develop a novel vehicle design that transports this type of technology into a sporting context while striving for considerable environmental benefits and integrating them into a society where the love of automobiles still has a strong following. The cutting-edge Industrial Design Structure (IDeS) methodology is used in this work, and a sample structure was created to demonstrate how the problems and technical limitations represented can be solved. The steps of the methodology are followed to shape the final product, with careful consideration given to the design of the styling component through the use of the Stylistic Design Engineering (SDE) method. With the ultimate goal of achieving sustainable driving pleasure, the study looks into whether recyclable materials can be used for the body and whether extremely light materials can be used for the chassis.